Membrane processes and their potential applications for fresh water provision in Vietnam. - Hung, Duong Cong; Nguyen, Nguyen Cong; Uan, Do Khac; Son, Le Thanh (Vietnam Journal of Chemistry, 2017)
Water treatment using membrane processes can be a pragmatic approach to mitigate the current fresh water scarcity in Vietnam. This paper provides a comprehensive review of mature and emerging membrane processes destined for water treatment. These processes include pressure-driven filtration (e.g. microfiltration, ultrafiltration, nanofiltration, and reverse osmosis), osmotically driven forward osmosis, and thermally driven membrane distillation. Fundamentals of the membrane processes were firstly provided. Additionally, the influences of membrane properties, module configurations, and operating conditions on fresh water production rate, membrane fouling propensity, and energy consumption of the membrane processes were analyzed. Finally, potential applications of the membrane processes to alleviate the fresh water scarcity in Vietnam were discussed. Keywords. membrane processes, wastewater treatment, wastewater reclamation, desalination, fresh water scarcity.